Investigating the Impact of Relative Cost on Motivation and Performance in Mathematics among BGCSE Students: A Qualitative Perspective - Mollowakgotla, Mpho (African Journal of Education and Practice, 2023)
Purpose: This study investigated the impact of "˜relative cost', a component of the Expectancy-Value Theory, on the performance of Botswana General Certificate of Secondary Education (BGCSE) mathematics. It also investigated the impact of social influences (parents, teachers, and peers) on students' mathematics perceptions. Methodology: In this qualitative research study, focus groups were conducted with a purposive sample of 40 students selected based on their performance from 10 randomly sampled secondary schools. The primary aim was to gain a comprehensive understanding of the students' experiences and perspectives. Findings: The results indicate that when engaging with mathematics, students perceive costs in the form of effort, stress, loss of time, and loss of preferable alternatives. Additionally, the study shows that teachers come in third after parents and peers in terms of influence on students' mathematics perceptions. Unique Contribution to Theory, Practice and Policy: Based on these findings, it is suggested that strategies be developed to mitigate these perceived costs and assist students in dealing with mathematics more effectively. This may include techniques for stress management, time management, or alternative teaching methods that make learning mathematics more pleasurable and less time-consuming.